Brazilian Food Handlers' Years of Work in the Foodservice and Excess Weight: A Nationwide Cross-Sectional Study - Fideles, Ingrid C.; Akutsu, Rita de Cássia C. de A.; Costa, Priscila R. de F.; Souza, Jamacy C.; Barroso, Rosemary da R. F.; Botelho, Raquel B. A.; Han, Heesup; Raposo, António; Ariza-Montes, Antonio; Vega-Muñoz, Alejandro; Zandonadi, Renata P. (Frontiers in Public Health, 2022)
This study aimed to evaluate the association between the years of work of food handlers in the foodservice and excess weight among Brazilian low-income food handlers. A total of 559 food handlers from all Brazilian regions were characterized using a questionnaire. Weight and height were measured to estimate the Body Mass Index and classify the individuals. The association between food handlers' years of work in the foodservice, anthropometric status, and other variables (gender, age group, educational level, participation in a government program and per capita income at home and energetic consumption) were performed using Pearson's chi-square test (p < 0.05). Multinomial logistic regression analyses were performed (p < 0.05) as well as sensitivity tests using the outcome continuously and transformed, excluding underweight individuals, in a multivariate linear regression model. Most of the sample was female (63.1%), aged between 21 and 40 years old (63.5%), and 53.3% had studied up to complete elementary school. Almost 41% of the food handlers had less than half the minimum wage per capita income. Of the evaluated individuals, 59.9% presented excess weight. There was an association with family per capita income (Odds Ratio - OR: 1.73; Confidence interval - CI95%: 1.09–2.75); handlers whose per capita income was ≤0.5 minimum wage had a 73% higher chance of obesity than those with higher income. Working in foodservive ≥3 years increased the chance of being overweight by 96% compared to those who work for <3 years (OR: 1.96; CI95%: 1.11–3.49). No significant association was found between the years of work of food handlers in the foodservice and obesity. Since work-related factors may contribute to the high prevalence of excess weight, including working in a food handling environment, the government and employers should consider workplace interventions. These would guide the food handlers in avoiding high rates of excess weight and their consequences on public health. Excess weight is an important driver of costs in the workplace associated with absenteeism, job change, and diseases. More studies are necessary to clarify the relationship between the factors related to work and the anthropometric status of food handlers since excess weight is multifactorial.